Myra Hess, Carnegie Hall, February 13, 1960 (The Friedberg Management, Inc.; New York, 2020)
Advertisement/handbill for a solo recital by pianist Myra Hess at Carnegie Hall, New York, on February 13, 1960, in an all-Beethoven program of the last three piano sonatas.